Pola Pengasuhan Anak Usia Dasar Pasca Perceraian dalam Perspektif Islam - Ibrahim Maulana Syahid Nur 'Ala; Tutik Hamidah; Tulus Setiyono (AL-ASASIYYA: Journal Of Basic Education, 2022)
The aim of this research is to describe the pattern of parenting post-divorce elementary age children in an Islamic perspective. This research is a library research which is descriptive analytic in nature. The approach used is a normative approach based on the principles of Islamic law based on the Qur'an and al-Hadith. The results of this study are as follows. Scholars have agreed that mothers have more rights to care for children of primary age. Because, the mother has a different parenting style than the father. A mother has more ability to provide a sense of security and comfort during the growth and development of elementary age children and has the ability to hold the mandate and responsibility during the formation of adab and character of elementary age children, and has the ability to become uswah hananah for her child in an effort to educate they become good Muslims in the future, as explained in surah at-Tahrim verse 6 and surah al-Baqarah verse 233.